Zastosowanie conjoint analysis w badaniach preferencji dotyczących oferty TV - Hetmańska, Swietłana; Zdobylak, Joanna (Applying conjoint analysis within TV offer preferences research, 2005)
Conjoint analysis is the method that is used for analysing preferences. For the first time it was used for psychometrical research by mathematical psychologist Luce and statistician Tukey. The main goal of this article is to illustrate conjoint analysis procedure with an example that deals with TV programs preferences. In this article there were also described advantages and disadvantages of some tools used in conjoint analysis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 76-86